Antibiotic Exposure Aggravates Bacteroides-Linked Uremic Toxicity in the Gut-Kidney Axis - Ray, Navin; Jeong, Hoyoung; Kwon, Dasom; Kim, Juil; Moon, Yuseok (Frontiers in Immunology, 2022)
Epidemiological and experimental evidence has implicated a potent link between antibiotic exposure and susceptibility to various diseases. Clinically, antibiotic treatment during platinum chemotherapy is associated with poor prognosis in patients with malignancy. In the present study, mucosal antibiotic exposure was assessed for its impact on renal distress as a sequela of platinum-based chemotherapy. Clinical transcriptome dataset-based evaluations demonstrated that levels of dysbiosis-responsive genes were elevated during renal distress, indicating pathological communications between gut and kidney. Experimentally, mucosal exposure to streptomycin aggravated platinum-induced renal tubular lesions in a mouse model. Moreover, antibiotic-induced dysbiosis increased susceptibility to gut mucosal inflammation, epithelial disruption, and bacterial exposure in response to cisplatin treatment. Further investigation of the luminal microbes indicated that antibiotic-induced dysbiosis promoted the dominance of Bacteroides species. Moreover, the functional assessment of dysbiotic microbiota predicted tryptophan metabolic pathways. In particular, dysbiosis-responsive Bacteroides acidifaciens was associated with the production of the uremic toxin indoxyl sulfate and renal injuries. The results of this study including bacterial community-based evaluations provide new predictive insights into the interorgan communications and interventions against dysbiosis-associated disorders.